Harmonisasi Hukum Internasional Pada Prinsip Common But Differentiated Responsibility dalam Hukum Nasional - Athya Athya (Universitas Muhammadiyah Purwokerto, 2019)
Abstract Efforts to prevent the growing concentration of GHGs that led to climate change began by the United Nations by establishing a regulation on the protection of the world climate system, first, the Convention on Climate Change is created in 1992. Secondly, Kyoto Protocol was established in 1997. Furthermore, at COP-21 resulted in Paris Agreement. These three arrangements make the Common but Differentiated Responsibility Principle as the basis for protecting the world climate system. This research is to review harmonization of international law on the Common but Differentiated Responsibility Principle in national law. This research uses normative law research. This research is a descriptive analysis with the secondary data obtained. All the data will be analysed qualitatively. Indonesia has implemented an international arrangement to address climate change caused by greenhouse gases into national law by ratifying the UNFCCC by Law Number 6 of 1994 about ratification of UNFCCC and the Kyoto Protocol by Act Number 17 of 2004 about ratification of Kyoto Protocol to the UNFCCC. Indonesia harmonized as a form of implementation of protocol kyoto contents through Law Number 32 of 2009 on Environmental Protection and Management. Keywords: Common but Differentiated Responsibility Principle; Law Harmonization Abstrak Upaya untuk mencegah meningkatnya konsentrasi GRK, pertama, Konvensi Perubahan Iklim dibuat tahun 1992. Kedua, didirikan Protokol Kyoto tahun 1997. Selanjutnya, pada COP-21 menghasilkan Perjanjian Paris. Ketiga pengaturan ini menjadikan Prinsip Tanggung Jawab Bersama dengan Tingkat Berbeda-beda sebagai dasar untuk melindungi sistem iklim dunia. Penelitian ini untuk meninjau harmonisasi hukum internasional tentang Prinsip Tanggung Jawab Bersama dengan Tingkat Berbeda-beda dalam hukum nasional. Penelitian ini menggunakan penelitian hukum normatif. Penelitian ini merupakan analisis deskriptif dengan data sekunder yang diperoleh. Semua data akan dianalisis secara kualitatif. Indonesia telah menerapkan pengaturan internasional untuk mengatasi perubahan iklim yang disebabkan oleh gas rumah kaca ke dalam hukum nasional dengan meratifikasi UNFCCC dengan Undang-Undang Nomor 6 Tahun 1994 tentang Pengesahan UNFCCC dan Protokol Kyoto oleh Undang-undang Nomor 17 Tahun 2004 tentang Pengesahan Protokol Kyoto Atas UNFCCC. Indonesia melakukan harmonisasi sebagai wujud implementasi isi Protokol Kyoto melalui Undang-undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup. Kata kunci: Harmonisasi Hukum, Prinsip Tanggung Jawab Bersama dengan Tingkat yang Berbeda-Beda